2021
DOI: 10.1021/acs.jpclett.1c03532
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic Dynamics between Valence, Nonvalence, and Continuum Electronic States in a Heteropolycyclic Aromatic Hydrocarbon

Abstract: Internal conversion between valence-localized and dipole-bound states is thought to be a ubiquitous process in polar molecular anions, yet there is limited direct evidence. Here, photodetachment action spectroscopy and time-resolved photoelectron imaging with a heteropolycyclic aromatic hydrocarbon (hetero-PAH) anion, deprotonated 1-pyrenol, is used to demonstrate a subpicosecond (τ1 = 160 ± 20 fs) valence to dipole-bound state internal conversion following excitation of the origin transition of the first vale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…DBS has been ubiquitously found in a variety of chemical or biological systems, ranging from the simplest diatomic molecules to the biological systems or molecular complexes. Recent spectroscopic studies have suggested that the DBS could be a primary candidate for the carrier of the diffuse interstellar species and/or the interstellar PAH anions, giving the enormous astrochemical implication. As the size of the dipole-bound orbital is almost identical to the de Broglie wavelength of the incoming electron, the electron attachment to neutral in the frame of DBS is extremely efficient. , In this aspect, it should be noted that the DBS has also long been conceived as the major doorway in the dissociative electron attachment (DEA) process where the slow electron is captured to be followed by the immediate rupture of the specific chemical bond. DEA is ubiquitously found, ranging from chemistry of the small environmentally important oxide species to radiative damages of biological genetic species of DNA/RNA double/single helices. Although the DEA dynamics have been much investigated in some elegant experimental or theoretical studies, the rather direct experimental evidence for the role of the DBS in the DEA has been quite rare to date. It should be noted here that the present work represents the anion chemistry of the isolated (or lightly solvated) systems as the chemistry/physics of the electron dynamics in heavily solvated or bulk medium is expected to be quite different. , The anionic DBS either loses the excess electron by the autodetachment process or undergoes the transformation into the more stable valence bound anion via the radiative and/or nonradiative transitions before it may be followed by the subsequent chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DBS has been ubiquitously found in a variety of chemical or biological systems, ranging from the simplest diatomic molecules to the biological systems or molecular complexes. Recent spectroscopic studies have suggested that the DBS could be a primary candidate for the carrier of the diffuse interstellar species and/or the interstellar PAH anions, giving the enormous astrochemical implication. As the size of the dipole-bound orbital is almost identical to the de Broglie wavelength of the incoming electron, the electron attachment to neutral in the frame of DBS is extremely efficient. , In this aspect, it should be noted that the DBS has also long been conceived as the major doorway in the dissociative electron attachment (DEA) process where the slow electron is captured to be followed by the immediate rupture of the specific chemical bond. DEA is ubiquitously found, ranging from chemistry of the small environmentally important oxide species to radiative damages of biological genetic species of DNA/RNA double/single helices. Although the DEA dynamics have been much investigated in some elegant experimental or theoretical studies, the rather direct experimental evidence for the role of the DBS in the DEA has been quite rare to date. It should be noted here that the present work represents the anion chemistry of the isolated (or lightly solvated) systems as the chemistry/physics of the electron dynamics in heavily solvated or bulk medium is expected to be quite different. , The anionic DBS either loses the excess electron by the autodetachment process or undergoes the transformation into the more stable valence bound anion via the radiative and/or nonradiative transitions before it may be followed by the subsequent chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Recent spectroscopic studies have suggested that the DBS could be a primary candidate for the carrier of the diffuse interstellar species and/or the interstellar PAH anions, giving the enormous astrochemical implication. [22][23][24][25] The anion chemistry/physics provoked by the electron-attachment is ubiquitously found not only in the atmospheric or interstellar species but also in a variety of biological/chemical processes such as photosynthesis, 26 destruction/relaxation of DNA bases, [27][28][29] or signaling of the fluorescent proteins. 30 As the size of the dipole-bound orbital is almost identical to the de Broglie wavelength of the incoming electron, the electron attachment to the neutral in the frame of DBS is extremely efficient.…”
mentioning
confidence: 99%
“…Although the molecular structure and chemical reactivity are primarily determined by the electronic configurations of the occupied valence orbitals, the excess electron held by the long-range attractive potentials plays a pivotal role in anion chemistry. , Although it is anticipated to be somewhat fragile, the nonvalence bound state (NBS), where the monopole-multipole interaction is largely responsible for the electron binding, has been ubiquitously found ranging from the simplest diatomic molecule to large biological molecules , and complexes. It has long been conceived that the NBS may play a critical role as the doorway into stable anion formation and/or chemical reactions. , In particular, the NBS is believed to be one of the important charge carrier to the formation of various interstellar anionic species as well. Further, the NBS has been considered as the doorway into dissociative electron attachment (DEA) where the slow electron is captured by the chemical system, followed by the immediate chemical bond rupture. …”
Section: Introductionmentioning
confidence: 99%
“…In this approach, the presence of optically allowed anion resonances yields an increase in the total photodetachment yield compared to that of the nonresonant direct photodetachment background. This method has mostly been used to probe the vibronic transitions of anion dipole-bound states which extend above the detachment threshold as well as anion resonances of aromatic molecules and is related to the 2D photoelectron spectroscopy introduced by Verlet and co-workers. The resolution of the total photodetachment spectrum is limited by the line width of the tunable laser and thus provides stringent benchmark for computations of autodetachment lifetimes. These measurements are compared to high-level electronic structure computations and line width modeling using OSM for the tetracene anion.…”
mentioning
confidence: 99%